Comparison of stratospheric evolution during the major sudden stratospheric warming events in 2018 and 2019 - Zheng Ma; Yun Gong; ShaoDong Zhang; JiaHui Luo; QiHou Zhou; ChunMing Huang; KaiMing Huang (Earth and Planetary Physics, 2020)
Using Modern-Era Retrospective analysis for Research and Applications, Version 2 (MERRA-2) data in the northern hemisphere at the 10 hPa level, we compared the stratospheric evolution of temperature and geopotential height during two major sudden stratosphere warming events (SSWs) that occurred in the Arctic winter of 2018 and 2019. In the prewarming period, poleward temperature-enhanced regions were mainly located around 120°E with a displaced vortex and around 120°E and 60°W with splitting vortices. The evolution of geopotential height indicated that these temperature-enhanced regions were both on the western side of high-latitude anticyclones. In the postwarming period, the polar vortex turned from splitting to displacement in the 2018 SSW but from displacement to splitting in the 2019 SSW. Both transitions were observed over the Atlantic region, which may have been caused by anticyclones moving through the polar region. Our findings revealed that the evolution of the anticyclone is important during SSWs and is closely related to temperature-enhanced regions in the prewarming periods and to transitions of the polar vortices in postwarming periods.